Technical evaluation of structural concrete made with coarse aggregate from construction and demolition waste (Research, Society and Development, 2022)
Civil construction sector is one of the largest producers of solid waste in the world and it is responsible to a enormous quantity of non-renewable natural resource consumption. An option to reduce the use of these resources is waste recycling as concrete aggregates. This article aims to present a study of Construction and Demolition Waste (CDW) use as recycled coarse aggregate (RCA) in structural concrete, focusing on the mix design effectiveness analysis of the concrete with RCA. The methodology consisted of establishing a reference mix design, then three concrete types were defined with total replacement of natural coarse aggregate by RCA. The amount of water and sand were constant and the percentage of cement varied in the proportions of 0%, 10% and 20%.  Results of the Slump Test showed that the use of superplasticizer leads to an increase of the workability of mix design containing RCA. Regarding compressive strength at 28 days, only the concrete with 20% of cement addition showed strength value near to the reference. The other concretes presented strength with low values when compared to the reference, being the biggest reduction equal to 21.60% (mix design with 0% of cement). The three studied concretes can be classified as structural, since the lowest obtained strength was equal to 25.34 MPa. The concrete with addition of 20% of cement presented strength properties similar to the reference concrete.